2007
DOI: 10.1177/1524838007301160
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities and Violence Against Women

Abstract: This article encourages readers to consider the cultural and societal influences that impact health and health disparities among women survivors of intimate partner violence (IPV). Health consequences caused by IPV are widely documented and broadly discussed. Connections between health disparities and IPV are also discussed as related to women of color. Cultural factors and societal influences are identified to provide the reader with greater awareness of how these issues intersect with and impact IPV. Finally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
91
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(92 citation statements)
references
References 59 publications
0
91
0
1
Order By: Relevance
“…79 Additional barriers include poverty, inadequate assessment tools, stereotyping and labeling women who experience IPV, lack of cultural competence, and language differences. 10 Other barriers reported in the literature are prior experiences with formal and informal services, hearing about negative interactions with formal services, lack of services, and finances. 11 Further, Black women may feel shame and guilt about their abuse due to lack of knowledge about IPV in their communities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…79 Additional barriers include poverty, inadequate assessment tools, stereotyping and labeling women who experience IPV, lack of cultural competence, and language differences. 10 Other barriers reported in the literature are prior experiences with formal and informal services, hearing about negative interactions with formal services, lack of services, and finances. 11 Further, Black women may feel shame and guilt about their abuse due to lack of knowledge about IPV in their communities.…”
mentioning
confidence: 99%
“…11 Further, Black women may feel shame and guilt about their abuse due to lack of knowledge about IPV in their communities. 10 In a predominantly Black sample of women, the reasons given for non-use of resources included barriers such as no money, insurance, or time; lack of knowledge of resources; partner preventing them from using resources; fear; confidentiality concerns; and tangible loss. 12 Thus, studies have identified various barriers to resource use among Black women and women from other racial/ethnic groups.…”
mentioning
confidence: 99%
“…Yet, Kothari et al (2012) found, in a sample of women survivors of partner violence (including SV) for which the police were involved, that African American women survivors were less likely to obtain protective orders than White women survivors. Such inconsistencies suggest the influence of contextual and cultural factors on the help-seeking behaviors of women survivors (Bent-Goodley, 2007; Boykins et al, 2010). …”
Section: Help-seeking and Service Needsmentioning
confidence: 99%
“…Further, a lower proportion of Black American compared to other couples were found to have obtained a restraining order (Vittes Sorenson, 2008). African American women experience barriers to such resource utilization including stigma, lack of cultural competence, racism and discrimination, and access to care and services (Bent-Goodley, 2007). Lack of resources may promote Black American women’s dependence on their male partners and may result in their increased risk of violence exposure.…”
Section: Use Of Community Resourcesmentioning
confidence: 99%